2010
DOI: 10.1007/s12032-010-9676-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ER, PgR, HER-2, Ki-67, cyclin D1, and nm23-H1 as predictors of pathological complete response to neoadjuvant chemotherapy for locally advanced breast cancer

Abstract: The purpose of this study was to evaluate the importance of biological markers to predict pathologic complete response (pCR) to neoadjuvant docetaxel plus epirubicin combination chemotherapy in patients with locally advanced breast cancer (LABC). Two hundred and twenty consecutive patients with LABC who had received neoadjuvant chemotherapy (NCT) with docetaxel and epirubicin from March 2006 to March 2009 were included in this retrospective study. The pre- and post-neoadjuvant chemotherapy (NCT) treatment expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 37 publications
(43 reference statements)
1
8
0
Order By: Relevance
“…Namely, it regulates the transition of the G1 phase into the S phase by dimerizing with CDK4/6. Any mutation, amplification or overexpression of this gene may alter cell cycle progression, which may contribute to tumorigenesis (21). Cyclin D1 overexpression contributes to increased chemotherapeutic resistance and protection from apoptosis, resulting in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, it regulates the transition of the G1 phase into the S phase by dimerizing with CDK4/6. Any mutation, amplification or overexpression of this gene may alter cell cycle progression, which may contribute to tumorigenesis (21). Cyclin D1 overexpression contributes to increased chemotherapeutic resistance and protection from apoptosis, resulting in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…In a published paper on the prognostic factors for breast cancer, the researchers classified patients into two groups using a cutoff value of 12% for Ki-67 expression, with the reasoning that 12% was the median Ki-67 expression value of patients without recurrence [10]. Another related study adopted 20% as the cutoff value to distinguish between low and high Ki-67 expression, without any valid explanation [11]. Some studies have suggested 25% as the cutoff value, the same value as our study, to classify low versus high Ki-67 expression, with the reasoning that 25% was the median value of Ki-67 expression for the cohort of patients [12].…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was quantitatively evaluated by two different observers in a blinded fashion (DP, RB) using light microscopy and counting the positive cells across three high power fields (HPF at 40x magnification), each containing about one hundred cells. Tumors were considered as positive for ER and PR if more than 10% of tumor nuclei were stained independently of staining intensity [ 10 , 23 ], because at the time of diagnosis this was the cutoff used to submit patients to Tamoxifen treatment. This is a deviation from the St. Gallen consensus and ASCO/CAP guidelines, which defined those cases presenting with more than 1% of tumor cells independently of staining intensity as hormonal receptor positive [ 7 , 24 ].…”
Section: Methodsmentioning
confidence: 99%